Fatty acid Constituent from the Heat Processed Roots of Panax ginseng - Chung, Ill-Min; Kim, Min-Young; Praveen, Nagella; Hong, Youn-Pyo; Ahmad, Ateeque (Asian Journal of Chemistry, 2012)
One compound n-tetratriacont-20,23-dienoic acid (1) along with b-sitosterol-b-Dglucopyranoside were isolated and identified from the heat processed roots of Panax ginseng. The structure of compound was elucidated with the help of 600 MHz NMR using 1D and 2D NMR (COSY, HSQC and HMBC) spectroscopic techniques aided by FABMS and IR spectra. The n-tetratriacont-20,23-dienoic acid (1) is reported for the first time from the roots of Panax ginseng.